Perancangan Lanskap Muara Cijulang Berbasis Coastal Resilience Sebagai Ekowisata - Putu Nala Viswa Dharma; Firmansyah (Universitas Nusa Putra, 2023)
Landscape Design of Cijulang Estuary Based On Coastal Resilience as Special Interest Ecotourism. Developing countries, including Indonesia, are currently demanding economic acceleration, demanding that more natural resources be exploited such as industrial development, ports and other infrastructure which are indicators of increased economic activity. Increased economic activity like this has contributed to accelerating damage to the estuary area, especially in Cijulang District, which is a coastal area and there are mangrove forests which are currently being affected by economic growth. The aims and objectives of this design thesis are to provide direction on spatial use in estuary areas that are based on spatial resilience of coastal areas . The design method in the Cijulang estuary area uses guidelines from La-Gro and Coastal Resilience , namely how to respond to social, response to tides, response to abrasion and siltation mitigation and response to economic activity on the environment. the estuary area began to be degraded, so the concept of ecoventour land design for resilience was developed which has four principles, namely ecological landscape, resilience, working productive landscape and adventurism which are implemented into the landscape design of the Cijulang estuary area with a scheme to change the spatial layout system which is considered to have violated regulation of estuary boundaries by proposing to return the green belt area to mangrove forest, proposing a pond system using silvofishry and developing potential outdoor spots to be used as special interest ecotourism (EMK) by developing facilities that can support the sustainability of mangrove conservation tourism as a form celebrate nature. These four principles are embodied as a spatial system in which there are guidelines and policies for the use of estuary areas such as determining protected and cultivated areas which can later control developments in the Cijulang estuary. The micro-scale design is carried out by proposing a design that focuses on four zones, namely: 1. Tourism Hub Zone 2. Lagoon conservation zone 3. River front park and observatory deck zone 4. Estuary Protection Zone